2020
DOI: 10.21037/hbsn.2020.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Liver venous deprivation versus portal vein embolization before major hepatectomy: future liver remnant volumetric and functional changes

Abstract: Background: We previously showed that embolization of portal inflow and hepatic vein (HV) outflow (liver venous deprivation, LVD) promotes future liver remnant (FLR) volume (FLR-V) and function (FLR-F) gain.Here, we compared FLR-V and FLR-F changes after portal vein embolization (PVE) and LVD.Methods: This study included all patients referred for liver preparation before major hepatectomy over 26 months. Exclusion criteria were: unavailable baseline/follow-up imaging, cirrhosis, Klatskin tumor, twostage hepate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 45 publications
(66 reference statements)
3
85
1
Order By: Relevance
“…Four monocentric studies comparing LVD to PVE were published in 2020 (1)(2)(3)(4). Despite technical variations, these reports are aligned towards greater FLR regeneration after LVD, both in terms of volume (1,2,4) and function (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Four monocentric studies comparing LVD to PVE were published in 2020 (1)(2)(3)(4). Despite technical variations, these reports are aligned towards greater FLR regeneration after LVD, both in terms of volume (1,2,4) and function (3).…”
mentioning
confidence: 99%
“…Unfortunately, data on LVD in cirrhotic patients are scarce. In the five most recent studies, cirrhotic patients were excluded in two (1,3), not treated by LVD in one (4) and were very few (n=2-3) in the others (2,9). Regrettably, no outcome data were reported in this subgroup of patients, even though no specific safety concerns were raised.…”
mentioning
confidence: 99%
“…This delay might be regarded as too long for a procedure supposed to hypertrophy the FLR faster. We must acknowledge that this delay could be significantly shortened since both volume and function hypertrophy of the FLR have been shown to occur as soon as 7 days after LVD [ 20 ]. Efforts should be made to shorten surgery planning, which remains difficult in daily practice especially in the context of COVID-19 pandemic with less resources.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of simultaneous embolization of portal vein and one or two hepatic veins, in order to increase the damage to the liver leading to increased hypertrophy of the contralateral parenchyma [ 16 , 17 , 18 ], with a kinetic growth rate of 16 ± 7 cc/day according to first reports [ 19 ]. Recently, first comparative data have been published regarding FLR volume and function gains [ 20 ]. All of them were in favor of greater regeneration after LVD versus PVE.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that LVD was safe and provided fast and important hypertrophy of the FLR at 3 weeks [5]. More recently, we showed that LVD could provide marked and very rapid increase not only in FLR volume but also in FLR function [6,7] assessed with 99m Tc mebrofenin hepatobiliary scintigraphy with SPECT which has been validated as a quantitative method for evaluating liver function [8].…”
Section: Introductionmentioning
confidence: 99%